A Novel Approach in Understanding and Retaining the Subject Concepts among Medical Undergraduates using Treasure Hunt Competition as a Tool: A Quasi-experimental Study - Shyamjith Manikkoth; B Deepa; Prajna V Raj; Bheemesh Vangalapati; Rathnakar P Urval; Suresh Vadakedom; Sajith Kumar Radhakrishnan (Journal of Clinical and Diagnostic Research, 2022)
Introduction: There is a need to incorporate innovative teaching methods other than conventional didactic lectures to generate interest of medical undergraduates in learning Pharmacology. Game-based Learning (GBL) is a new strategy in medical education that can create a fun based atmosphere for learning. Aim: To assess the effectiveness of GBL as a tool in learning process and in memory retention of the knowledge acquired in pharmacology using treasure hunt competition. Materials and Methods: The quasi-experimental study was conducted on 4th semester MBBS students of Kanachur Institute of Medical Sciences, Mangaluru, Karnataka, India, from February to March 2019, as a part of the Advanced Course in Medical Education (ACME) project work, Medical Council of India. Entire phase II students (N=150) were included in the study. Students were divided into the GBL group and the Facilitated Learners (FL) group. Both groups were exposed to their respective GBL and FL based learning. Before and after the respective GBL and FL sessions, a pretest and two post-test multiple choice questions based tests were conducted. The second post-test was conducted one month later as a surprise one. Thereafter, a questionnaire was given to pen down the perceptions about GBL. Pretest and post-test marks were analysed by one-way Analysis of Variance (ANOVA) followed by the Tukey-Kramer test. Perceptions about GBL were entered in percentage. Results: The mean scores of the GBL group were significantly more (p-value <0.001) as compared to the FL group in both the post-tests. In their feedback about GBL, the students appreciated the usefulness of this innovative way of learning pharmacology. Conclusion: The GBL is an effective tool to teach pharmacology to medical undergraduates.